2021
DOI: 10.3389/fendo.2021.667170
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vascular Cells in Pancreatic Beta-Cell Function

Abstract: Insulin-producing β-cells constitute the majority of the cells in the pancreatic islets. Dysfunction of these cells is a key factor in the loss of glucose regulation that characterizes type 2 diabetes. The regulation of many of the functions of β-cells relies on their close interaction with the intra-islet microvasculature, comprised of endothelial cells and pericytes. In addition to providing islet blood supply, cells of the islet vasculature directly regulate β-cell activity through the secretion of growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 123 publications
1
28
0
Order By: Relevance
“…An abnormal endothelial function may cause a mismatch between insulin release and blood flow adjustment in islet microcirculation, resulting in dysregulated insulin secretion. Actually, a complex endothelial‐β‐cell functional axis has been postulated in pancreatic islets (Burganova et al, 2021 ; Hogan & Hull, 2017 ; Narayanan et al, 2017 ; Peiris et al, 2014 ). Islet endothelial cells produce factors (e.g., hepatocyte growth factor or connective tissue growth factor), that enhance β‐cell differentiation and proliferation (Oliveira et al, 2018 ; Riley et al, 2015 ) and others that influence insulin biosynthesis and/or release, such as NO, endothelin‐1 and extracellular matrix molecules (Gregersen et al, 1996 ; Hogan & Hull, 2017 ; Johansson et al, 2009 ; Nikolova et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal endothelial function may cause a mismatch between insulin release and blood flow adjustment in islet microcirculation, resulting in dysregulated insulin secretion. Actually, a complex endothelial‐β‐cell functional axis has been postulated in pancreatic islets (Burganova et al, 2021 ; Hogan & Hull, 2017 ; Narayanan et al, 2017 ; Peiris et al, 2014 ). Islet endothelial cells produce factors (e.g., hepatocyte growth factor or connective tissue growth factor), that enhance β‐cell differentiation and proliferation (Oliveira et al, 2018 ; Riley et al, 2015 ) and others that influence insulin biosynthesis and/or release, such as NO, endothelin‐1 and extracellular matrix molecules (Gregersen et al, 1996 ; Hogan & Hull, 2017 ; Johansson et al, 2009 ; Nikolova et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is a hormone naturally secreted by the body that helps our cells, particularly muscle cells, liver cells, adipose cells, and brain cells, absorb glucose from food to be converted into energy for all biological processes and functions [ 125 , 126 ]. In normal conditions, insulin is secreted by pancreatic β-cells, then released into the bloodstream.…”
Section: Anti-diabetic Effect Of Isorhamnetinmentioning
confidence: 99%
“…ECs can directly affect β-cell function by upregulating insulin secretion and promoting β-cell survival via the secretion of soluble factors such as hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF)-A (36) and ECM proteins (37). Although the contribution of EC to islet endocrine function has been well described in the literature, the role of PC has recently been emphasized (35). Pericytes are abluminal mural cells embedded in the BM-ECM of blood vessels and play a key role in regulating endocrine niche homeostasis and function (35,37).…”
Section: Cell Roommates Of the Endocrine Pancreatic Nichementioning
confidence: 99%
“…Although the contribution of EC to islet endocrine function has been well described in the literature, the role of PC has recently been emphasized (35). Pericytes are abluminal mural cells embedded in the BM-ECM of blood vessels and play a key role in regulating endocrine niche homeostasis and function (35,37). Indeed, Landsman et al, in a series of ablation experiments, reported the role of pericytes in β-cell expansion during the neonatal stage and in the maintenance of β-cell maturation and function in adulthood (38)(39)(40), regulating the production and deposition of islet ECM components and promoting the expression of β-cell genes including Ins1, Mafa, and Glut2 (41).…”
Section: Cell Roommates Of the Endocrine Pancreatic Nichementioning
confidence: 99%
See 1 more Smart Citation